Modification in the properties of SnO2 and TiO2 nanocomposite thin films by low energy ion irradiation. Issue 193 (13th October 2018) - Kumar, Vikas; Jaiswal, M. K.; Gupta, R.; Kulriya, P. K.; Asokan, K.; Sulania, Indra; Ojha, S.; Kumar, Rajesh
Abstract: The nanocomposite thin films of Tin oxide (SnO2 ) and Titanium dioxide(TiO2 ) were deposited on silicon and ITO substrate by RF magnetron sputtering technique using sintered pellet formed by mixing SnO2 and TiO2 in the mass percentage ratio of 25:75 respectively. These thin films were irradiated with low energy carbon negative ion (C −1 ) at varying fluence from 5e14 to 1e17 ions/cm 2 to create modifications in the material properties. Crystallinity and phase transformation was studied by X-ray diffraction (XRD) technique. An increase in crystalline size was observed from 13.33 nm to 27.38 nm with an increase of ion fluence. Also the strain values were found to decrease from 1.485 to 0.507. Surface morphology was characterized by Atomic Force Microscopy (AFM) technique that confirmed the grain size dependence on ion fluence. The optical properties of thin films were investigated using UV/Visible Spectroscopy and decreasein band gap (3.91-2.55eV) was observed. The variation in optical band gap is due to the formation of defect states and phase transformation. Rutherford Backscattering Spectrometry (RBS) was used to confirm the change in elemental composition. A decrease in the width of the tin peak was observed with increase in the ion fluence that shows a decrease in thickness of thin films from 230 ± 2 nm to 220 ± 2 nm. The modification in the properties can be attributed to the formation of defects, vacancies and temperature spike generated in the samples due to irradiation.